Rapid Genomic Characterization of SARS-CoV-2 by Direct Amplicon-Based Sequencing Through Comparison of MinION and Illumina iSeq100TM System - Hourdel, Véronique; Kwasiborski, Aurelia; Balière, Charlotte; Matheus, Séverine; Batéjat, Christophe Frédéric; Manuguerra, Jean-Claude; Vanhomwegen, Jessica; Caro, Valérie (Frontiers in Microbiology, 2020)
Global human health is increasingly challenged by emerging viral threats, especially those observed over the last twenty years with coronavirus-related human diseases, such as the Severe Acute Respiratory Syndrome (SARS) and the Middle East Respiratory Syndrome (MERS). Recently, in late December 2019, a novel Betacoronavirus, SARS-CoV-2, originating from the Chinese city of Wuhan, emerged and was then identified as the causative agent of a new severe form of pneumonia, COVID-19. Real-time genome sequencing in such viral outbreaks is a key issue to confirm identification and characterization of the involved pathogen and to help establishing public health measures. Here, we implemented an amplicon-based sequencing approach combined with easily deployable next-generation sequencers, the small and hand-held MinION sequencer and the latest most compact Illumina sequencer, the iSeq100™ system. Our results highlighted the great potential of the amplicon-based approach to obtain consensus genomes of SARS-CoV-2 in just a few hours, in particular to explore clinical samples with low viral loads. Both these mobile next-generation sequencers are proven to be efficient to obtain viral sequences and easy to implement, with a minimal laboratory environment requirement, providing useful opportunities in the field and in remote areas